Metaphors for advice messages in online sermons delivered by global Islamic preachers - Cipto Wardoyo; Zalifa Nuri (Universitas Islam Negeri Ar-Raniry, 2026)
Research on metaphor in religious discourse is essential, particularly in practical contexts such as preaching, where metaphor serves as a key vehicle for conveying abstract spiritual experiences and moral guidance. Despite its importance, metaphor use in religious settings remains underexplored, especially in digitally mediated forms of religious communication. This study investigates the use of metaphorical language in twenty Islamic online sermons focused on the theme of family. A balanced corpus was compiled, comprising sermons from ten male and ten female Islamic preachers, with the aim of analyzing the metaphors embedded in advice-oriented discourse. The inclusion of both genders allows for a comparative examination of potential differences in metaphorical expression between male and female preachers. The findings reveal that female preachers employ metaphors more frequently than their male counterparts. Furthermore, structural metaphors drawing on source domains related to future benefits—such as building, finance, and plants—are prominently used by both groups when conveying advice. These results suggest that while gender may influence the frequency of metaphor use, certain conceptual metaphors are shared across genders in the context of Islamic family-oriented preaching. The study contributes to the growing field of metaphor studies in religious discourse and highlights the need for further research on gender and metaphorical framing in digital religious settings.